2004
DOI: 10.1291/hypres.27.771
|View full text |Cite
|
Sign up to set email alerts
|

Additive Beneficial Effects of the Combination of a Calcium Channel Blocker and an Angiotensin Blocker on a Hypertensive Rat-Heart Failure Model

Abstract: The present study was undertaken to examine the effects of a calcium channel blocker, azelnidipine (1 mg/kg/day), an angiotensin converting enzyme (ACE) inhibitor, temocapril (10 mg/kg/day), an angiotensin II type 1 (AT1) receptor blocker (ARB), olmesartan (5 mg/kg/day), and their combination on Dahl salt-sensitive rats (DS rats) developing heart failure with preserved systolic function. DS rats were fed a high-salt diet (8% NaCl) from 7 weeks of age and progressively developed hypertension. Although monothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Recently, it was reported that the administration of a combination therapy with ARB and CCB exerted protective effects on organs in a rodent model. 23,24 Although CCBs and ARBs are considered first-line antihypertensive drugs in Japan, the rate of attaining the target BP level by the administration of monotherapy with either drug is B12-40%. 25,26 According to a Japanese cross-sectional survey, the combination therapy with a CCB and an ARB is the most prescribed treatment for hypertensive patients in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that the administration of a combination therapy with ARB and CCB exerted protective effects on organs in a rodent model. 23,24 Although CCBs and ARBs are considered first-line antihypertensive drugs in Japan, the rate of attaining the target BP level by the administration of monotherapy with either drug is B12-40%. 25,26 According to a Japanese cross-sectional survey, the combination therapy with a CCB and an ARB is the most prescribed treatment for hypertensive patients in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 In short, the mouse heart was set with 10% formaldehyde overnight and embedded in paraffin. Five-mm-thick sections were cut and stained with Sirius red stain to measure the interstitial fibrosis area.…”
Section: Estimation Of Cardiac Fibrosismentioning
confidence: 99%
“…However, AZ may also reduce oxidative stress induced by some other pathway, because its effects were still observed in angiotensin II type 1 (AT1) receptor knock-out mice ( 11 ). Furthermore, combined administration of AZ with a RAS inhibitor elicited more potent renal protective activity than either agent alone in hypertensive rats complicated with heart failure ( 13 ). From these results, concomitant use of AZ plus a RAS inhibitor is expected to be more effective than use of either agent alone.…”
Section: Introductionmentioning
confidence: 99%